Building Environments for Female Sex Trafficking Victims: A Parametric Design Approach - Foteini Papadopoulou; Silvio Carta; Ian Wyn Owen (Athens Journal of Architecture, 2024)
This paper presents findings on the use of computational design techniques to analyse and develop a building environment based on a set of defined design principles. In this study, we explored and established the design principles of a building environment for female victims of sex trafficking that contribute to the overall recovery and reintegration of these women into society. Additionally, we examined and evaluated the use of parametric design as a computational tool to support the development of a model for designing these building environments. We address this issue by creating a set of guidelines based on data research and literature review and testing data-driven techniques, including generative design and models for self-organising floor plans. The paper explores the benefits as well as the potential disadvantages of such design approaches by comparing them to this set of desired guidelines. Finally, we present preliminary findings from this analysis and suggest further research directions.